Diagnostic Performance of Magnetic Resonance Cholangiopancreatography (MRCP) for Biliopancreatic Cancer - Hassan Hossary, Sandy; Anas Zytoon, Ashraf; Eid, Mohamed; Hamed, Ahmed; Sharaan, Mohamed; Abd El-Maguid Ebrahim, Ahmed (Current Medical Imaging, 2014)
Introduction: MRCP has achieved widespread success as a diagnostic tool for biliopancreatic cancer. Aim of the study: is to assess the diagnostic quality and overall accuracy of MRCP techniques for the evaluation of biliopancreatic cancer. Patients and Methods: from 266 patients (115 male, 151 female; mean age 50), 63 suspected for biliary tree or pancreatic diseases cancer and histopathologically confirmed, were enrolled in this study. MRCP protocols applied for imaging of biliary and pancreatic tree were; T2-weighted Fast spin echo (FSE) sequence on the axial plane, three-dimensional, fatsuppressed, heavily T2-weighted FSE sequence with multislab acquisition mode, two-dimensional thick single slab projectional images, three-dimensional reconstruction algorithms. Results: among the patients, jaundice and abdominal pain were the commonest clinical complaints. Three-dimensional, fat-suppressed, heavily T2-weighted FSE sequence with multislab acquisition mode shows a significant (p<0.05) improvement in accuracy to from 88.1% to 92.9% compared to two-dimensional thick single slab projectional images. Moreover, there is a significant increase in sensitivity from 90.5% to 95.2% was seen; specificity, too, increased from 85.7% to 90.5%. Furthermore, Overall bile duct visualization with the 3D fat-suppressed, heavily T2 FSE with multislab acquisition technique was rated significantly higher (mean score = 4.7) versus 2D thick single slab projectional images (mean score= 4) (P < 0.05). Conclusion: MRCP plays a critical role in the differential diagnosis with significant improvement in the accuracy of the diagnosis of biliopancreatic cancer.
Keywords: MRCP